2007
DOI: 10.1007/s00535-006-2003-y
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic stenting versus surgical gastroenterostomy for palliation of malignant gastroduodenal obstruction: a meta-analysis

Abstract: Endoscopic stenting may be a feasible alternative to surgery for the palliation of inoperable malignant gastroduodenal obstruction, with a high clinical success and low morbidity rate. Additional well-designed randomized controlled trials with larger sample sizes are expected to further reinforce this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0
13

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(112 citation statements)
references
References 31 publications
6
93
0
13
Order By: Relevance
“…Surgical palliation of GDO is associated with high mortality (up to 7%) and morbidity rates (10%-16%) even with the recent advances in surgical techniques (5). Metallic stent placement has been increasingly used as a minimally invasive method with lower mortality and morbidity rates than surgical GJ (3,7,8,12,14,15). It has high technical success rates similar to surgical palliation (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical palliation of GDO is associated with high mortality (up to 7%) and morbidity rates (10%-16%) even with the recent advances in surgical techniques (5). Metallic stent placement has been increasingly used as a minimally invasive method with lower mortality and morbidity rates than surgical GJ (3,7,8,12,14,15). It has high technical success rates similar to surgical palliation (8).…”
Section: Discussionmentioning
confidence: 99%
“…It has high technical success rates similar to surgical palliation (8). It also results in earlier oral intake and shorter hospital stay than surgical GJ with lower costs (6,7,14,15). Nevertheless, the need for reintervention seems to be more common after stent placement due to recurrent obstructive symptoms because of tumor ingrowth and stent migration (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…There have been mixed reports on the technical and clinical success rates, cost of procedure and complication rates. More commonly, studies found no difference between technical and clinical success rates [49][50][51]53], but in a meta-analysis of 307 procedures by Hosono et al [45], clinical success was higher in the stenting group. A recent 10-year retrospective study of stenting versus GJ by Khashab et al [46 •• ] found statistically higher rates of technical success in the GJ group (96 vs. 99 %).…”
Section: Emerging Technologiesmentioning
confidence: 97%
“…Most studies agree that stenting provides the following advantages over laparoscopic or open gastro-jejunostomy: shorter operative time, shorter hospital stay and decreased time to oral intake [44][45][46][47][48][49][50][51][52]. However, they almost universally report decreased patency of stents with higher rates of recurrent obstruction and need for re-intervention [46 •• , 49, 50, 53].…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Placement of self expandable metallic stents is associated with higher clinical success rates, less morbidity, shorter times from the procedure to starting oral intake, lower rates of delayed gastric emptying, and shorter hospital stay than palliative surgery. 13,14 This article reviews the use of this minimally-invasive therapeutic option in the palliative treatment of unresectable malignant GOOs.…”
Section: 25mentioning
confidence: 99%